Extended resection including adjacent organs and Ki-67 labeling index are prognostic factors in patients with retroperitoneal soft tissue sarcomas. Issue 1 (December 2016) - Morizawa, Yosuke; Miyake, Makito; Shimada, Keiji; Hori, Shunta; Tatsumi, Yoshihiro; Nakai, Yasushi; Anai, Satoshi; Tanaka, Nobumichi; Konishi, Noboru; Fujimoto, Kiyohide
Abstract Background Because retroperitoneal soft tissue sarcomas (RPS) are extremely rare, there is a significant lack of clinicopathologic information to optimize the treatment strategy. The aim of this study was to evaluate the prognostic factors in RPS, with particular focus on the Ki-67 labeling index (LI). Methods We included the data from a total of 23 patients who received treatment for primary RPS at a single center. The variables analyzed in this study included tumor size, histological type, malignancy grade, necrosis, mitosis, and Ki-67 LI. Kaplan-Meier and Cox proportional regression analyses of overall survival (OS) were performed to identify significant prognostic variables. Results Of the 23 patients who underwent surgical resection, 9 (39 %) underwent simple resection of the tumor and 14 (61 %) extended resection including the adjacent organs. In the univariate analysis, a simple tumor resection and a high Ki-67 LI were associated with shorter OS. The multivariate analysis revealed that simple tumor resection and a high Ki-67 LI were independent negative prognostic factors for OS. Conclusions Our results suggested that combined resection of RPS and its adjacent organs improved OS. Pathologically, a high Ki-67 LI was significantly associated with negative prognosis.